Uterine fibroid embolization: An analysis of clinical outcomes and impact on patients’ quality of life - Ubaldi Nicolò; Andrea Tipaldi Marcello; Giannini Andrea; Golia D’Augè Tullio; Caserta Donatella; Simone Laganà Antonio; Grasso Giacomo; Zolovkins Aleksejs; Ronconi Edoardo; Rossi Michele (Open Medicine)
Uterine fibroids (UF) affect up to 70–80% of women by age 50 and are associated with heavy menstrual bleedings, pelvic discomfort, and reduced quality of life. Uterine artery embolization (UAE) is a minimally invasive procedure that aims to reduce fibroid-related symptoms and improve patients’ quality of life.